Product development : an engineer's guide to business considerations, real-world product testing, and launch - Tennant, David V. (John Wiley & Sons, Inc., 2022)
"My formal academic training began as a student of mechanical engineering. Simultaneously, I worked part time as a designer to pay for my education. In this case, my work allowed me to see how products were developed to the lower level where I was doing the technical drawing. And my engineering education helped me learn the limits of materials, think about product technical features, and how to apply mathematical formulas to solve technical problems. However, nowhere did I learn about how products are really developed. What drives a company to success? How do companies know which products will be accepted in the marketplace? What is a marketplace or a market segment? As a result, my education and early work experience taught me a lot about applying engineering principals, but I had no knowledge of marketing, sales, business finance, C-level executive support, or how R&D (research and development) and the other areas are supposed to all work together. I simply (and naively) believed that new products were developed and launched by the engineering department. The product that had the better design would always be preferred by consumers. Since those days in college, and my early career in engineering, I have come a long way to understanding that product development is a multi-faceted effort involving many diverse groups and talents. It is so much more than R&D or engineering."--